HIGHLY ACTIVE W-H2SO4/HZSM-5 CATALYST FOR DIRECT CONVERSION OF METHANE INTO AROMATIC - Kusmiyati Kusmiyati; Nor Aishah Saidina Amin; W.A. Siswanto (Reaktor, 2007)
Dehydroaromatization of methane (DHAM) under non oxidative condition was studied over tungsten loaded HZSM-5 catalysts to produce aromatic hydrocarbons. The catalysts were prepared by impregnation method using different conditions: in neutral and acidified solution. The activity of W/HZSM-5 prepared by neutral solution and W-H2SO4/HZSM-5 prepared in acidified condition were compared. The results showed that the optimum activity of W-H2SO4/HZSM-5 catalyst exceeded that of W/HZSM-5 catalyst. The effect of Si/Al ratio of W- H2SO4/HZSM-5 catalyst was also studied. The W- H2SO4/HZSM-5 catalyst with Si/Al ratio = 30 was found to be the most promising for the DHAM reaction. The remarkable activity of the catalyst is attributed to the presence of dual effects: suitable content of octahedral polymeric and tetrahedral monomeric tungstate species accompanied by proper amount and strength of acid sites in the catalyst.